The role of Kisspeptin signaling in Oocyte maturation - Masumi, Saeed; Lee, Eun Bee; Dilower, Iman; Upadhyaya, Sameer; Chakravarthi, V. Praveen; Fields, Patrick E.; Rumi, M. A. Karim (Frontiers in Endocrinology, 2022)
Kisspeptins (KPs) secreted from the hypothalamic KP neurons act on KP receptors (KPRs) in gonadotropin (GPN) releasing hormone (GnRH) neurons to produce GnRH. GnRH acts on pituitary gonadotrophs to induce secretion of GPNs, namely follicle stimulating hormone (FSH) and luteinizing hormone (LH), which are essential for ovarian follicle development, oocyte maturation and ovulation. Thus, hypothalamic KPs regulate oocyte maturation indirectly through GPNs. KPs and KPRs are also expressed in the ovarian follicles across species. Recent studies demonstrated that intraovarian KPs also act directly on the KPRs expressed in oocytes to promote oocyte maturation and ovulation. In this review article, we have summarized published reports on the role of hypothalamic and ovarian KP-signaling in oocyte maturation. Gonadal steroid hormones regulate KP secretion from hypothalamic KP neurons, which in turn induces GPN secretion from the hypothalamic-pituitary (HP) axis. On the other hand, GPNs secreted from the HP axis act on the granulosa cells (GCs) and upregulate the expression of ovarian KPs. While KPs are expressed predominantly in the GCs, the KPRs are in the oocytes. Expression of KPs in the ovaries increases with the progression of the estrous cycle and peaks during the preovulatory GPN surge. Intrafollicular KP levels in the ovaries rise with the advancement of developmental stages. Moreover, loss of KPRs in oocytes in mice leads to failure of oocyte maturation and ovulation similar to that of premature ovarian insufficiency (POI). These findings suggest that GC-derived KPs may act on the KPRs in oocytes during their preovulatory maturation. In addition to the intraovarian role of KP-signaling in oocyte maturation, in vivo, a direct role of KP has been identified during in vitro maturation of sheep, porcine, and rat oocytes. KP-stimulation of rat oocytes, in vitro, resulted in Ca2+ release and activation of the mitogen-activated protein kinase, extracellular signal-regulated kinase 1 and 2. In vitro treatment of rat or porcine oocytes with KPs upregulated messenger RNA levels of the factors that favor oocyte maturation. In clinical trials, human KP-54 has also been administered successfully to patients undergoing assisted reproductive technologies (ARTs) for increasing oocyte maturation. Exogenous KPs can induce GPN secretion from hypothalamus; however, the possibility of direct KP action on the oocytes cannot be excluded. Understanding the direct in vivo and in vitro roles of KP-signaling in oocyte maturation will help in developing novel KP-based ARTs.